Clinical profile of patients diagnosed with supraventricular tachycardia: a descriptive study at a tertiary care hospital - Harris, Rinee; Sahay, Ravindra Nath (International Journal of Advances in Medicine, 2022)
Background: Supraventricular tachycardia is a clinical syndrome characterized by a rapid tachycardia with an abrupt onset and termination. The objective of our study was to determine and assess the clinical profile, electrocardiographic and echocardiographic of patients diagnosed with supraventricular tachycardia. Methods: This cross-sectional study was conducted in the department of general medicine, Dr DY Patil medical college and hospital, Navi Mumbai from April 2020 till October 2021, in which we included patients diagnosed with any type of supra-ventricular tachycardia and excluded hemodynamically unstable patients. Results: In the present study, of the 45 cases, atrial fibrillation was the most common mechanism of SVT, diagnosed in 47% of the patients. Next most common was AVNRT (22%) and AVRT (18%). In addition, atrial tachycardia was diagnosed in 9% of the patients and atrial flutter was diagnosed in 4%. Mean age of the patients was 34.5 years, ranging from 13 to 68 years and 56% were males. It was observed that palpitation was the most common symptoms (91%). On ECG, no abnormalities were detected in 64%, while left ventricular hypertrophy (18%) and prolonged corrected QT (18%) were the most common abnormalities. On echocardiography, no abnormality was detected in 78% of the patients. Furthermore, 49% of the patients achieved normal sinus rhythm with a single dose of adenosine infusion and 33% of the patients required another dose of adenosine infusion. Conclusions: Palpitation is common presentation symptom. Most of patients had good response to medication treatment especially adenosine therapy, additional treatment was required in few patients.